Analysis of climate time series (Revista de Ciências Agroveterinárias, 2015)
The purpose of this study was to time analyze the series of temperature and precipitation in the period from 1961 to 2011 from the EPAGRI/CIRAM weather station records located in Lages-SC, Brazil. The corrections of failures were made up of readings from the regional weighting method, and a proposed alternative model of linear regression with lowest MSE. The methods of Fourier Transform, Wavelet Transform and statistical test of Mann-Kendall were used. The presence of annual cycles for the mean monthly temperature and cycles ranging from 3 to 5 years for monthly accumulated precipitation were detected. There is a positive trend in the pattern of monthly cumulative rainfall from the El Niño of 1983, according to the Mann-Kendall test, and in minimum and maximum temperatures in some months of both absolute and relative to the monthly average.
Keywords: climate change; trend; wheater; mathematical modeling.